Travelling through Text: Representation of Toba Batak Cultures in Suhunan’s Sordam in Promoting Toba Tourist Destinations in North Sumatra, Indonesia - Bertova Simanihuruk; Asmyta Surbakti; I Nyoman Darma Putra; Eddy Setia (Universitas Muhammadiyah Semarang, 2023)
Literature and tourism are intertwined in a reciprocal relationship, where many literary works draw inspiration from the world of tourism, and many tourist attractions are promoted in literary works. This article investigates the representation of Toba Batak cultures depicted in Sordam (2010), a novel by Suhunan Situmorang, and its relationship with promoting Toba tourist destinations. By employing qualitative approach, this study collects data from the novel and analyses them using the literary tourism approach and intertextuality theory. The results show that Sordam frames its narration through three main Toba Batak cultures: saur matua death ceremony, mangongkal holi tradition, and spirit summoning ritual. It is done so by inserting some intermingled stories to support its narrations, such as the story of Lake Toba occurrence from two perspectives, cultural materials, historical notes, myths, and magical realism. By creatively providing natural and cultural attractions of Toba Batak, Sordam persuades readers to travel through text and intertextuality. In this viewpoint, Sordam presents itself directly or indirectly as a medium for promoting Toba tourist destinations. Hence, by exploring readers' experiences traveling through text, this article strengthens the reciprocal relationship between literary works and the tourism world.